2016
DOI: 10.1007/s12160-016-9769-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain Status, Nicotine Withdrawal, and Expectancies for Smoking Cessation Among Lighter Smokers

Abstract: Background-Chronic pain and tobacco smoking are both highly prevalent and comorbid conditions, and chronic pain may pose a barrier to smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…Indeed, tobacco smoking has been identified as a unique risk factor in the development of chronic pain [72; 75], pain has been shown to motivate smoking behavior [20; 21], current smoking has been linked to more severe pain and functional impairment among treatment-seeking pain patients [33], and there is mounting evidence that pain may impede smoking cessation [24; 25; 83]. Although it has been suggested that chronic exposure to nicotine and tobacco smoke may increase sensitivity to pain over time [22, 70], these results indicate that nicotine can also produce short-term analgesic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tobacco smoking has been identified as a unique risk factor in the development of chronic pain [72; 75], pain has been shown to motivate smoking behavior [20; 21], current smoking has been linked to more severe pain and functional impairment among treatment-seeking pain patients [33], and there is mounting evidence that pain may impede smoking cessation [24; 25; 83]. Although it has been suggested that chronic exposure to nicotine and tobacco smoke may increase sensitivity to pain over time [22, 70], these results indicate that nicotine can also produce short-term analgesic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, consistent with evidence that pain can motivate smoking, there are some data to suggest that pain may impede smoking cessation. For example, smokers in pain (relative to no pain) tend to endorse greater difficulty when attempting to quit and less confidence in their ability to remain abstinent during future quit attempts (Ditre, Kosiba, Zale, Zvolensky, & Maisto, under review; Zale et al, 2014). In addition, both acute pain reactivity (Nakajima & al’Absi, 2011) and positive chronic pain status (Waldie, McGee, Reeder, & Poulton, 2008) have been linked with smoking relapse trajectories.…”
Section: Bidirectional Relations Between Pain and Tobacco Smokingmentioning
confidence: 99%
“…Indeed, smokers with chronic pain who endorse greater withdrawal severity during past quit attempts have been shown to anticipate more severe withdrawal/negative affect during future quit attempts (Ditre, Kosiba, et al, under review). Consistent with evidence that past cessation failures may erode confidence for future success (Carey & Carey, 1993; Kirchner, Shiffman, & Wileyto, 2012), smokers in pain have also been shown to report lower levels of self-efficacy and greater perceived barriers to quitting, in part due to having experienced more severe withdrawal and greater difficulty during previous quit attempts (Ditre, Kosiba, et al, under review; Zale et al, 2014). Thus, smokers with comorbid anxiety, depression, and pain may be more likely to encounter difficulty maintaining abstinence, which may engender expectations that ultimately serve to undermine future quit attempts.…”
Section: Implications For Smoking Cessationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of tobacco smoking among individuals in pain (28%–68%; Goesling, Brummett, & Hassett, 2012; Michna et al, 2004; Orhurhu, Pittelkow, & Hooten, 2015; Patterson et al, 2012) far exceed those observed in the general population (18%; CDC, 2014), and smokers with chronic pain (vs. no chronic pain) are nearly two times more likely to meet diagnostic criteria for nicotine dependence (Zvolensky, McMillan, Gonzalez, & Asmundson, 2009). Smokers who live with pain have also been shown to consume more cigarettes per day and report less confidence in their ability to quit than pain-free smokers (Ditre, Kosiba, Zale, Zvolensky, & Maisto, 2016; Zale, Ditre, Dorfman, Heckman, & Brandon, 2014). Despite emerging evidence that tobacco smokers with comorbid pain may constitute a recalcitrant subgroup that faces unique barriers to smoking cessation (Ditre, Langdon, Kosiba, Zale, & Zvolensky, 2015; Zale & Ditre, 2013), the extent to which individuals perceive their pain and smoking behavior to be interrelated remains understudied.…”
Section: Introductionmentioning
confidence: 99%